Virtual screening for potential inhibitors of β(1, 3)-D-glucan synthase as drug candidates against fungal cell wall. (1st January 2020) - Farhadi, Zinat; Farhadi, Tayebeh; Hashemian, Seyed MohammadReza
Abstract: Background: To enhance the outcome in patients with invasive candidiasis, initiation of an efficient antifungal treatment in a suitable dosage is necessary. Echinocandins (e.g. caspofungin) inhibit the enzyme β(1, 3)-D-glucan synthase of the fungal cell wall. Compared to azoles and other antifungal agents, echinocandins have lower adverse effects and toxicity in humans. Echinocandins are available in injectable (intravenous) form. Methods: In this study, to identify the novel oral drug-like compounds that affect the fungal cell wall, downloaded oral drug-like compounds from the ZINC database were processed with a virtual screening procedure. The docking free energies were calculated and compared with the known inhibitor caspofungin. Four molecules were selected as the most potent ligands and subjected to hydrogen bonds analysis. Results: Considering the hydrogen bond analysis, two compounds (ZINC71336662 and ZINC40910772) were predicted to better interact with the active site of β(1, 3)-D-glucan synthase compared with caspofungin. Conclusion: The introduced compound in this study may be valuable to analyze experimentally as a novel oral drug candidate targeting fungal cell walls.